DIABETES SELF MANAGEMENT TERHADAP HBA1C DAN KADAR GULA DARAH PADA KELOMPOK PREDIABETES SEBELUM DAN SESUDAH INTERVENSI - Ali, Kartini Muhamad; Muhammad, Rusny (Media Penelitian dan Pengembangan Kesehatan, 2024)
Prediabetes is a condition in which a person has blood glucose levels that are higher than normal but not yet high enough to be classified as diabetes. The aim of this study was to determine the effect of diabetes self-management on blood sugar and HbA1c levels in the prediabetes group before and after intervention in the Kalumpang Community Health Center working area, Ternate. This research uses the Pre-Experimental method (one-group pre-post test design with control). Based on the data, the number of samples in this study was 25 which included control and intervention groups with a total of 50 samples. Inclusion criteria are individuals who are willing to be respondents, cooperative individuals, individuals aged 45 – 54 years, individuals who are willing to fill out a 24 hour food recall questionnaire, individuals who have HbA1c levels: ≥5.7% - <6.5%, GDP : ≥100- <126 mg/dl and GD2PP :≥140- <200 mg/dl. Meanwhile, the exclusion criteria are individuals who are not willing to be respondents and individuals who are not cooperative. Data analysis to test the results of treatment before and after treatment used the Paired T-Test. The study's results showed a significant difference between the patient's blood sugar and HbA1c before and after the intervention. Compared with the control, there was a significant difference in blood sugar levels and HbA1c between the intervention and control groups. The main finding of this study is that diabetes self-management has an impact on HbA1c and blood sugar levels in the prediabetes group.